2021
DOI: 10.1038/s41379-021-00862-2
|View full text |Cite
|
Sign up to set email alerts
|

Myxoid pleomorphic liposarcoma—a clinicopathologic, immunohistochemical, molecular genetic and epigenetic study of 12 cases, suggesting a possible relationship with conventional pleomorphic liposarcoma

Abstract: Myxoid pleomorphic liposarcoma is a recently defined subtype of liposarcoma, which preferentially involves the mediastinum of young patients and shows mixed histological features of conventional myxoid liposarcoma and pleomorphic liposarcoma. While myxoid pleomorphic liposarcoma is known to lack the EWSR1/FUS-DDIT3 fusions characteristic of the former, additional genetic data are limited. To further understand this tumor type, we extensively examined a series of myxoid pleomorphic liposarcomas by fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…Molecular findings are in line with those of the adult PLPS and are associated with a complex karyotype with multiple (whole chromosomal) gains and losses, with the most frequent mutations being in TP53 and NF1 (see also Table 1 ) [ 77 , 105 , 107 , 108 , 109 ]. Peng et al found loss of chromosomes 17 and 22, with deletion of RB1 [ 77 ].…”
Section: Liposarcomasupporting
confidence: 77%
See 4 more Smart Citations
“…Molecular findings are in line with those of the adult PLPS and are associated with a complex karyotype with multiple (whole chromosomal) gains and losses, with the most frequent mutations being in TP53 and NF1 (see also Table 1 ) [ 77 , 105 , 107 , 108 , 109 ]. Peng et al found loss of chromosomes 17 and 22, with deletion of RB1 [ 77 ].…”
Section: Liposarcomasupporting
confidence: 77%
“…MPLPS is a new entity within pediatric liposarcomas, first described in 2009 by Allagio et al and genomically seen as a distinct subtype of liposarcoma in the current WHO (5th edition, 2020) [ 79 , 83 , 93 , 107 ]. These lesions are rare, although they have a higher incidence in the pediatric population in comparison to adults [ 77 ].…”
Section: Liposarcomamentioning
confidence: 99%
See 3 more Smart Citations